2004
DOI: 10.1111/j.0197-6664.2004.00040.x
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Community‐Based Programs for Families: Conceptualization and Measurement*

Abstract: A conceptual model for evaluating community-based program sustainability is presented, along with a 53-item Program Sustainability Index (PSI). Structural equation modeling (SEM) and principal axis factor analysis indicate strong support for each of the seven elements of the PSI. When considered as an overall model, six of the seven framework elements were retained. Internal consistency for each subscale was acceptable, and acceptable performance validity was demonstrated when the subscales were contrasted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
146
1
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(166 citation statements)
references
References 20 publications
4
146
1
9
Order By: Relevance
“…In a very broad way, sustainability is defined as "whether or not something continues to work over time" [27]. Other approaches are more detailed, with some scholars considering sustainability as addressing the program continuity in its entirety, while others addressed continuity of specific program components [26], improvement of community capacity, programs institutionalisation [19] or the capacity of the program to continuously respond to community issues [28]. These divergent definitions attest that definitional consensus has not been made, and congruent sustainability factors are considered by various scholars or practitioners.…”
Section: Community Based Programs Sustainability and Sustainability Fmentioning
confidence: 99%
See 1 more Smart Citation
“…In a very broad way, sustainability is defined as "whether or not something continues to work over time" [27]. Other approaches are more detailed, with some scholars considering sustainability as addressing the program continuity in its entirety, while others addressed continuity of specific program components [26], improvement of community capacity, programs institutionalisation [19] or the capacity of the program to continuously respond to community issues [28]. These divergent definitions attest that definitional consensus has not been made, and congruent sustainability factors are considered by various scholars or practitioners.…”
Section: Community Based Programs Sustainability and Sustainability Fmentioning
confidence: 99%
“…Unfortunately, a comprehensive overview of community based program sustainability factors does not exist [28,46,47] [18,50].…”
Section: Community Based Programs Sustainability and Sustainability Fmentioning
confidence: 99%
“…Les explorations des modèles socio-écologiques ont ajouté une concentration sur les niveaux d'intervention multiples pour la promotion de la santé (Edwards et coll., 2004 ;Hancock, 1993). Quoique nous sachions maintenant que de nombreuses interventions visant des secteurs et des niveaux multiples ont de fortes chances de créer un changement durable (Edwards et coll., 2004 ;Crozier Kegler et Miner, 2004 ;Mancini et Marek, 2004), il reste encore beaucoup à apprendre sur les déterminants de la santé et les stratégies connexes cruciales pour les environnements qui promeuvent la santé publique.…”
Section: Resultsunclassified
“…However, its inherited bias is that the research design was based on relatively weak self-reports, as the informants who were the key person in the involved projects would lead to the rating being inflated. Mancini and Marek [15] constructed a framework to evaluate community-based programme sustainability with seven major elements including a 29-item Program Sustainability Index (PSI). However, the interplay of each sustainability element showed that some precede other factors, since they put all the indicators in an equivalent relationship.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Staff involvement and integration: Include the committed, qualified staff in programme design, implementation, evaluation and decision making [15]. (C23) 4.…”
mentioning
confidence: 99%